Investigation of Ni as Zn substitute in CZTS thin film solar cell - Quek, Ka Jun (2018)
Thin film solar cell technology based on Cu2ZnSn(S,Se)4 (CZTSSe) holds great promise due to the abundancy of its constituent elements and their environmentally friendly nature. In recent years, developments in achieving higher device performance have been halted due to the inherent Voc deficit of CZTSSe. Recent progress in cation substitution of CZTSSe with other metals such as Cd and Ag have shown promising results. However, these two metals are not ideal due to their toxicity and rarity. One of the other alternatives is Ni as a substitute for Zn because it is more abundant and less toxic than Cd and Ag. Therefore, in this study, investigation on the crystal structure, morphology, optical and electrical properties of Cu2NixZn1-xSnS4 (CNZTS) thin film layers were conducted to study their viability as absorber for thin film solar cell. In addition, two spray methods (dynamic and static mode) were also investigated based on scanning electron microscopy (SEM) and current-voltage characteristics to find the best method to synthesize CNZTS. The highest efficiency achieved was around 5.45% for pure Cu2ZnSnS4 (CZTS) device using static mode, meanwhile the nickel-substituted samples behave like a metal instead of semiconductor when the Ni is substituted. X-ray diffraction (XRD), Raman spectroscopy and ultraviolet-visible light spectroscopy (UV-Vis) were done to investigate the crystal structure and band gap of the CNZTS. There are 3 main peaks found among the films, which correspond to the kesterite CZTS and Cu2NiSnS4 (CNTS) phases. From Raman, presence of mixed CNTS and CZTS phases are observed, while at x = 1.0 secondary phases are formed and become dominant. Energy-dispersive X-ray spectroscopy (EDX) was also done to check elemental composition of CNZTS in the thin film layer. AC Hall measurement was also conducted and it showed that the CNZTS layers have turned into n-type semiconductor when Ni substitution is more than 20% and also the carrier concentration increased significantly. Finally, based on these results, few suggestions to improve the thin films properties are proposed.